Assessing reproductive effects and epigenetic responses in Austrolebias charrua exposed to Roundup Transorb®: Insights from miRNA profiling and molecular interaction analysis - Pagano, Antônio D.; Nunes, Leandro S.; Domingues, William B.; da Silveira, Tony L.R.; Kütter, Mateus T.; Schneider, Augusto; Kremer, Frederico S.; Junior, Antonio S.V.; Amaral, Marta G.; Gonçalves, Natiéli M.; Bellido-Quispe, Dionet K.; Volcan, Matheus V.; et al. (Elsevier, 2024)
This study examines the effects of Roundup Transorb® (RDT) exposure on reproductive functions and ovarian miRNA expression in Austrolebias charrua. Exposure to RDT (at 0.065 or 5 mg. L−1 for 96 h) significantly disrupts fertility, evidenced by changes in fertilization rates and egg diameter. Profiling of ovarian miRNAs identified a total 205 miRNAs in A. charrua. Among these, three miRNAs were upregulated (miR-10b-5p, miR-132–3p, miR-100–5p), while ten miRNAs were downregulated (miR-499–5p, miR-375, miR-205–5p, miR-206–3p, miR-203a-3p, miR-133b-3p, miR-203b-5p, miR-184, miR-133a-3p, miR-2188–5p) compared to non-exposed fish. This study reveals that differentially expressed miRNAs are linked to molecular pathways such as steroid hormone biosynthesis, lipid and carbohydrate metabolism, bioenergetics, and antioxidant defense. It also analyzes molecular interactions between miRNAs and target genes during RDT exposure in annual killifish, providing insights into biomarkers in ecotoxicology. Moreover, it provides scope for developing environmental health assessment models based on epigenomic endpoints, supporting the protection of biodiversity and ecosystem services through the quantification of stress responses in living organisms exposed to pesticides.
Keywords: Biodiversity; Ecotoxicogenomics; Glyphosate; Interactome analysis; MicroRNA sequencing; Reproductive toxicology